Welding parameter optimization using Taguchi method and Grey Relational Analysis for Gas Metal Arc Welding A1008 butt-joint - Mattar, Zainal Abidin Shah (2013)
Gas Metal Arc Welding (GMAW) is one of the most important metal joint processes in metal fabrication industries. In this technique and all types of welding process, the optimal selection of welding parameter is vital in achieving high quality joints. In this study, welding current, welding voltage and welding speed are selected as welding parameter specifications. Orthogonal array of Taguchi method were performed to drive the objective function in relation to parameter of weld joint strength and then followed by Grey Relational Analysis (GRA) to solve the multi-response optimization problem. The results then were verified to check the quality using Analysis of Variance (ANOVA). The Finite Element Analysis (FEA) of residual stresses in butt-joint of two welding parameter is performed with ANSYS software and the optimum welding parameters gained from optimization was used in this study. A moving heat source model based on Goldak’s double-ellipsoid heat flux distribution is presented. The residual stresses have been calculated and the result showed that optimum welding parameters reach a value of 266 MPa and increase to value of 270 MPa for non-optimum welding parameter. The residual stress distribution and magnitude in the axial direction was obtained and the results show good agreement between the optimum and non-optimum welding process parameter.